Ibn Hazm dan Imam Asy-Syafi’i Membincang Istimna’ - M. Inzah (Asy-Syari’ah : Jurnal Hukum Islam, 2016)
Most of the Ulema forbid the act of masturbation. One of the prominent scholars who forbid schools and denouncing acts of masturbation / istimna is the Imam Shafi’i. Legal basis cling Imam Shafi’i law in setting masturbation/ masturbation / istimna ‘This is the Word of Allah. in the Qur’an Surat al-Muminun verse: 5-6. Where in the verse there are only two things that are allowed for in jima ‘, with wives and slaves. So, masturbation is forbidden because it is not mentioned in the verse of Al-Qur’an. And it is reinforced in the next paragraph in the same letter. In addition Imam Shafi’i also seen in terms of moral ethics which turns the act of masturbation does not include actions are commendable. Ibn Hazm one of the scholars of the school of Zahiri said that masturbation / masturbation it makruh law and no sin [La Isma fihi]. However, according to masturbation / masturbation can be forbidden because of damage ethics and nobility were commendable. Ibn Hazm take legal argument with the statement that people who touched his own cock with his left hand is allowed by the ijma ‘(agreement of all the clergy). By this consideration that there is no additional than the legal permissible, except for deliberate release sperm [at-Ta’ammud li Nuzul al-Maniy] during masturbation. This act can not be prohibited altogether. Because the Word of God in the Qur’an Surat al-An’am: 119, Allah has explained what is forbidden him and the Qur’an does not find the verse which states about the prohibition of the act of masturbation. Although in terms of moral ethics Ibn Hazm also consider masturbation as licentious acts. While the medical view on masturbation, in reality the masturbation impact studies prove that it can reduce and prevent prostate cancer is alsoone cause of cancer death affected humans the disease. In psikologipun bit much there are benefits to be felt and there are also disadvantages to be derived as well from committing the act of masturbation. But various trends, impacts or the effects would be back for the offender itselfs in addressing this masturbation.